THE ELEVENTH GRADE STUDENTS’ ABILITY IN USING QUESTION TAG IN SMA NEGERI 1 LINTONG NIHUTA - Hutasoit, Feranita; Ginting, Fiber Yun Almanda (Kairos English Language Teaching Journal, 2021)
Grammar is a description of certain organizing aspects of a written particular language. One of the grammar topic is question tag. Question tag is a mini question which we often put at the end of a sentence. The purpose of this study is to describe the ability of the eleventh grade students of SMA Negeri 1 Lintong Nihuta in using question tag. This study is a qualitative study with descriptive research. The population of this study is the eleventh grade students of SMA Negeri 1 Lintong Nihuta in Academic Year 2020/2021. The sample is 50 students. The instrument for collecting data is a test concerning question tag which consist of 20 multiple choice and 10 for completion form. The test is done in order to know the ability of students in using question tag. Based on result of the data analysis, the percentage of the student’s ability is devided three parts high category, moderate category and low category. The result shows that 2 students (4%) belong to high score category, 40 students (80%) to moderate category, and 8 students (16%) to low category. The mean score is 83.56, it is 84% of the total students who can do the test well with 42 students who got score above 72. The writer concludes that the eleventh grade students of SMA Negeri 1 Lintong Nihuta are able in using question tag